The construction of the universality of English within Saudi Arabian education contexts. Issue 5 (3rd September 2017) - Alhamdan, Bandar; Honan, Eileen; Hamid, M. Obaidul
ABSTRACT: Discourses of the universality of English and its role in individual mobility and social development abound in the literature; these discourses have contributed to the global spread of English and to the development of English Language Teaching as a profession. Despite the ubiquity of the discourses of the value and universality of English, there has been limited research on how these discourses unfold in local contexts, how these discourses are reproduced or appropriated, and how these are translated into teaching and learning artefacts (e.g. policies and textbooks) and practices by teachers and students. This paper explores the construction of the discourse of the universality and value of English within education policies, curricular documents, and textbooks used in Saudi Arabian schools, and how these discourses then play out within teacher/student interactions in a rural Bedouin-dominated classroom. Our aim is to contribute to the understanding of global English and its discourses taking a local, situated perspective.